2019
DOI: 10.1001/jamaoto.2018.3692
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Sleep Endoscopy Findings in Supine vs Nonsupine Body Positions in Positional and Nonpositional Obstructive Sleep Apnea

Abstract: IMPORTANCE The anatomic mechanisms underlying positional vs nonpositional obstructive sleep apnea (OSA) are poorly understood and may inform treatment decisions. OBJECTIVE To examine drug-induced sleep endoscopy (DISE) findings in the supine vs nonsupine body positions in positional and nonpositional obstructive sleep apnea. DESIGN, SETTING, AND PARTICIPANTS A cross-sectional study of 65 consecutive eligible adults with OSA undergoing DISE without marked tonsillar hypertrophy, including 39 with positional OSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Further study is needed with the DISE results. Third, although body position has been found to have a definite effect on upper airway collapsibility 7,27,28 , this study has a limitation that the effect of body position was not taken into account. This is because PM was measured during natural whole-night sleep and includes all body positions such as supine, right lateral, left lateral and prone, whereas DISF was evaluated only in the supine position during drug-induced sleep.…”
Section: Discussionmentioning
confidence: 96%
“…Further study is needed with the DISE results. Third, although body position has been found to have a definite effect on upper airway collapsibility 7,27,28 , this study has a limitation that the effect of body position was not taken into account. This is because PM was measured during natural whole-night sleep and includes all body positions such as supine, right lateral, left lateral and prone, whereas DISF was evaluated only in the supine position during drug-induced sleep.…”
Section: Discussionmentioning
confidence: 96%
“…Patients with an AHI of 15-30 exhibited less severe lateral pharyngeal wall obstruction in the lateral position, but the obstruction increased in those with an AHI exceeding 30. Yalamanchili, et al 23) found that the oropharyngeal wall was the principal obstruction site in OSA patients, especially when sleeping in the lateral position. Thus, changes in sleep position may affect the principal upper airway obstruction site.…”
Section: Discussionmentioning
confidence: 99%
“…In a population of mostly nonobese adults, Yalamanchili et al have showed a greater likelihood of anteroposterior airway narrowing (velum, tongue base, and epiglottis) in the supine position in both positional and non-positional OSA. In non-positional OSA, there was a higher degree of oropharyngeal lateral wall collapse in the lateral position [ 18 ]. In the study of Lee et al, they have found that oropharyngeal lateral wall collapse did not show significant improvement after position change (70.6% in supine vs. 60.0% in lateral).…”
Section: Discussionmentioning
confidence: 99%